Corporate Governance and Risk Disclosures of Banks in Ghana - Buabeng, S. (University of Ghana, 2018)
This study examines the effects of corporate governance on risk disclosure of banks in Ghana using a sample size of 21 banks over an eight-year period (2007-2014). Using annual data of the banks the study estimates risk disclosure scores to measure risk disclosure levels and corporate governance mechanisms as surrogates for corporate governance. It employs panel regression analysis to investigate the linkage between risk disclosures of the banks and corporate governance, while controlling for some bank specific characteristics. The study reveals that the trend of risk disclosures in banks’ annual reports in Ghana is quite high and increased over the period. The results however indicate that institutional ownership, audit committee independence and board size are not significantly associated with bank risk disclosure. Risk management committee size and board independent had positive and significant relationship with bank risk disclosure. However, a robust test of joint corporate governance variables had positive but insignificant relationship with bank risk disclosures indicating a weak relationship. This result thus does not provide evidence to support the agency theory in Ghana’s banking sector concerning the disclosures of risk in corporate annual reports. The results also reveal that bank size, return on assets, auditor type and IFRS adoption have positive and significant relationship with risk disclosures of banks in Ghana. Local or foreign bank however tends to have a negative and significant relationship with bank risk disclosures.
MPhil. Accounting
Keywords: Corporate Governance; Risk Disclosure; Bank; Ghana